Multivariate analyses of the biometric features from Philippine sardines - Implications for the phylogenetic relationships of the freshwater Sardinella tawilis (Teleostei, Clupeomorpha) - Samonte, Irene E. (Animo Repository, 2009)
Philippine sardines are members of the commercially important Sardinella genus (Family Clupeidae). Sardines are mostly marine species with a very few exception like the Philippine freshwater sardine, Sardinella tawilis, of Lake Taal. This species is believed to have immigrated from Balayan Bay some 250 years ago. To determine the relationship of freshwater S. tawilis to the marine forms, 35 biometric features were investigated. The variables were subjected to univariate (mean, standard deviation and coefficient of variance) and multivariate analyses [Principal Component Analysis (PCA) and Hierarchical Cluster Analysis]. Results from univariate tests revealed that the number of ventral fin ray can discriminate Sardinella lemuru from the rest of the sardines. Multivariate PCA, on the other hand, showed discrete separation of the marine sardines. Sardinella tawilis, however, cannot be clearly separated from the marine species, Sardinella albella. The same clustering was recovered in HCA, thus providing evidence that S. albella is the closest marine relative of the freshwater S. tawilis. © 2009 Blackwell Verlag GmbH.